Dampak Penggunaan Gadget Terhadap Perkembangan Kognitif Anak Usia Dini - Dewita Rumaseb; Yufilda Tlonaen; Erlin Sonlai; Neti Manao; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Early childhood cognitive development is an important aspect that forms the basis for the ability to think, solve problems and learn at a later stage. The aim of this research is to determine the impact of gadget use on the cognitive development of children aged 5-6 years. The method in this research is quantitative. The sampling technique was purposive sampling, namely children aged 5-6 years. The respondents for this research were 15 children aged 5-6 years at PAUD Taruna Elim Kuanino, Kupang City. The data collection technique uses a questionnaire with instruments in the form of a gadget use scale and a cognitive development scale. The data analysis technique is simple linear regression. The results of these findings found that the impact of gadget use on the cognitive development of children aged 5-6 years was 12.8%. It is hoped that parents and educators can limit the use of gadgets in young children.